2016
DOI: 10.1089/lap.2015.0618
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dilation Methods in Percutaneous Nephrolithotomy: Which One Is More Successful?

Abstract: None of the dilation methods was significantly superior in terms of surgical success, efficiency, or safety. Although balloon dilation was advantageous with respect to time parameters, the role of surgical experience should not be ignored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 19 publications
0
17
0
1
Order By: Relevance
“…According to our eligibility criteria, one RCT and five CCTs were included in this systematic review and meta-analysis. [16][17][18][19][20][21] Basic study design characteristics and quality assessments of the included studies are provided in table 1. In each of the included studies, groups were relatively homogeneous in terms of stone location, size and shape.…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our eligibility criteria, one RCT and five CCTs were included in this systematic review and meta-analysis. [16][17][18][19][20][21] Basic study design characteristics and quality assessments of the included studies are provided in table 1. In each of the included studies, groups were relatively homogeneous in terms of stone location, size and shape.…”
Section: Literature Searchmentioning
confidence: 99%
“…All studies reported transfusion rates [16][17][18][19][20][21] but only one reported that balloon dilation can significantly reduce the need for blood transfusion. 21 The remaining five studies did not verify this finding and therefore could not reach the same conclusion.…”
Section: Literature Searchmentioning
confidence: 99%
“…To conclude for the dilatation techniques, comparative studies showed that none of the aforementioned dilatation methods were significantly better than another, and the choice depends on the clinical situation, stone condition and surgeon's preference …”
Section: Pcnlmentioning
confidence: 99%
“…63,64 To conclude for the dilatation techniques, comparative studies showed that none of the aforementioned dilatation methods were significantly better than another, and the choice depends on the clinical situation, stone condition and surgeon's preference. 65,66 Size of tract Currently, there are at least two nomenclature for PCNL tract size, which might lead to confusion (Table 2). 67,68 Although the stone clearance rate is good with the standard PCNL, mini-PCNL has been shown to have less blood loss, reduced hospital stay and more tubeless procedures without compromising the stone clearance rate or increasing the infective complications.…”
Section: Dilatation Of Tractmentioning
confidence: 99%
“…Biz çalışmamızda; operasyon süresinin uzamasının, çocuklarda PNL ameliyatı yapılırken göz önünde bulundurulması gereken artmış kan kaybı için bağımsız bir risk faktörü olduğunu saptadık. Bu verilerin doğruluğunun teyit edilmesi amaçlı daha çok sayıda hasta verileri ile prospektif çalışmaların yapılması gerektiğini düşünmekteyiz.olduğuna dair hiçbir kanıt bulamadıklarını ifade etmişlerdir(28). Bizim çalışmamızda da single step (tek aşamalı) dilatasyon ve Amplatz aşamalı dilatasyon metodları arasında kan kaybı riski üzerinde anlamlı farklılık saptanmamıştır.…”
unclassified